Institutional antecedents of public service motivation: Administrative regime and sector of economy. Issue 1 (3rd April 2021) - Prysmakova, Palina
Abstract: New findings on public service motivation in the public sector often contradict the previous ones. Such deviations are regularly explained by the uniqueness of the institutional settings of the sample. Yet, only few studies have compared PSM across different institutional environments; even less is known about nonprofit employees. We can only speculate that their institutional antecedents of PSM resemble their public counterparts because of the public benefit orientation of their work. Utilizing a Most Similar Systems Design method to test the institutional propositions on a sample of public and nonprofit employees from two different institutional environments, the present study confirms that (a) PSM variation of public employees across different countries can be explained by a state‐level institutional variation, and (b) for PSM of nonprofit employees, the institutional environment of a country may be irrelevant. The results confirm earlier propositions of the sectoral differences of PSM and urge us to revisit the generalizability of the previous findings of PSM relationships because they can be limited by the similarity of the observed systems.